AN EVIDENCE BASED REVIEW ON AYURVEDIC MANAGEMENT OF TAMAKA SHWASA (BRONCHIAL ASTHMA) - Pravin, Masram; Vedika, Ade; K. S, Patel; S., Rajagopala (International Journal of Ayurveda and Pharma Research, 2015)
Ayurveda is the major systems of indigenous medicines and as all of us know it is a science of life. The ancient sages discovered different kinds of Ayurvedic medicines after continuous study, observations, experiments, reflections, trials and judgments. Ayurveda gives us this knowledge of health. Unlike many diseases, which can be attributed to the life style of modern man, asthma is an ancient illness. Childhood Bronchial Asthma has multifactor causation Geographical location, environmental, racial, as well as factors related to behaviors and life-styles are associated with the disease. Tamaka Shwasa is a disease described in Ayurvedic texts that shows close resemblance with bronchial asthma on the basis of clinical manifestations. There is no cure for Asthma as per the Conventional Medical Science. Ayurvedic medicines can be a potential and effective alternative for the treatment against the bronchial asthma. Ayurvedic medicines are used for the treatment of diseases globally so that people all over the world can keep faith on it on the basis of scientific evidences.The present study was a review on the management of Tamaka-Shwasa (Childhood bronchial asthma) who were being managed through Ayurvedic approach that includes a combination of Shodhana Chikista, Ayurvedic drugs, lifestyle management and wholesome diet. Ayurvedic drugs include the respiratory tonics and naturally occurring bronchodilator and immune-modulator. Thus, study result concluded that the Shodhana, Shaman, herbal and herbo-minerals compound drug has got significant anti asthmatic properties.